Translation and Commentary on Three Articles by H. Polakowsky on the State of Costa Rican Archaeology in 1888 - Rojas Garro, Myrna (2026)
This contribution is based on the translation from German into Spanish of three articles published by Polakowsky in 1888, more than a century ago, in which he informs the academic world of the time about the creation of the National Museum of Costa Rica, the very little that was known about the country’s archaeology, the consolidating practice of huaquerismo (grave robbery), and the striking gold objects found in Chiriquí that are stylistically related to those in the Museum. In this nascent practice of scientific archaeology in our region, it is worth recognizing the relevance of some topics while others have been discarded through more recent research. Also interesting is the use of photography in his presentation at the Seventh Congress of Americanists, Berlin 1888, and its positive feedback on Alfaro’s institutional work. As a special contribution by the translators, a profile of the author is provided to place him and his work in historical context. The translation also includes numerous annotations to help the reader better appreciate the documents.